KERANGKA KERJA MANAJEMEN HUBUNGAN MASYARAKAT DALAM MENCIPTAKAN MADRASAH UNGGUL - subairi, subairi (Institut Agama Islam Negeri (IAIN) Palopo, 2019)
The progress of a madrasa or educational institution needs to be supported jointly by all elements, small environment (family), madrasas (educational institutions), and the environment (community). These three elements must be combined, synergized, with the hope of producing results or good quality education outcomes. This expectation must of course be carried out / improved by the education provider (madrasa). in the sense that madrasas play an active role in establishing communication with elements of the environment (community), both with teachers, education personnel, student guardians, or with surrounding communities. in realizing this good relationship, the implementation of community relations management is needed. Madrasas in the current era really require an active role from the community in supporting its success, both in educating, providing great opportunities and giving birth to capable, independent sons of the nation. so that later, students can adapt to the environment, in establishing good communication. Management of public relations management is very important, so that communication links between educational institutions and the surrounding environment (community) generally encourage and participate in supporting the success of an educational institution.